2014
DOI: 10.1089/chi.2014.0051
|View full text |Cite
|
Sign up to set email alerts
|

Home Food Availability, Parental Dietary Intake, and Familial Eating Habits Influence the Diet Quality of Urban Hispanic Children

Abstract: Home food availability, parental diet, and familial eating habits seem to play an important role in the diet quality of children. Interventions targeting family education on healthful dietary habits at home could have a positive impact on children's diet quality and overall health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
81
1
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 19 publications
7
81
1
6
Order By: Relevance
“…Findings were similar among urban Hispanic adolescents living in the USA. This suggests that not only parents play a role in their children's access and availability to foods and beverages, but at same importance in their preferences for those items, demonstrating that adolescents might mimic their parents'/caregivers' dietary behaviors [33]. The present study did not find a significant association between family meals and girls' dietary intake as hypothesized.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Findings were similar among urban Hispanic adolescents living in the USA. This suggests that not only parents play a role in their children's access and availability to foods and beverages, but at same importance in their preferences for those items, demonstrating that adolescents might mimic their parents'/caregivers' dietary behaviors [33]. The present study did not find a significant association between family meals and girls' dietary intake as hypothesized.…”
Section: Discussioncontrasting
confidence: 59%
“…However, an increase on the intake of the core food items and a decrease on the intake of the non-core food items were observed, in relation to those that reported sharing at least three family meals per week. On the other hand, Santiago-Torres et al [33] found no positive associations between family meals and dietary quality of the adolescents. However, they found an inverse association between family meals while watching TV and their children's diet quality.…”
Section: Discussionmentioning
confidence: 92%
“…In related work with 187 US Hispanic children, Santiago-Torres et al 23 found that the availability of sugarsweetened beverages was associated with lower Healthy Eating Index score. Similarly, Couch et al 13 reported a positive association between the availability of low-calorie foods and Dietary Approaches to Stop Hypertension score, whereas the availability of high-calorie foods was inversely associated with Dietary Approaches to Stop Hypertension score among children.…”
Section: Discussionmentioning
confidence: 99%
“…Many Latino families prefer FCCH to other EEC settings due to cultural preferences for family-like care, flexible hours and lower costs, thus making FCCH an ideal setting for obesity prevention targeting Latino families and children (16) . Research indicates that healthful eating and PA practices implemented in child-care settings can positively affect children's healthful behaviours in this setting (17)(18)(19)(20) . Moreover, this effect on healthful behaviours may possibly transfer to the home environment (21,22) .…”
mentioning
confidence: 99%
“…While more research is needed to examine whether behaviours learned in FCCH transfer to the home and family, the potential for transferability is especially important given that Latino children's home environment is often characterized by obesogenic parenting practices (23) . Although a growing number of studies have focused on FCCH as a setting for promoting early healthful eating and PA (17)(18)(19)(20)(24)(25)(26) , to our knowledge no study has examined Latino parents' perceptions of their children's eating and PA experiences in FCCH run by Latino providers. Therefore, the purpose of the current qualitative study was to examine Latino parents' perceptions of their children's eating and PA experiences while at home and at FCCH.…”
mentioning
confidence: 99%